KONSTRUKSI WACANA AGAMA DI MEDIA KOMIK DIGITAL - Rahmatika, Arina; Mu’afa, Maimunatul (representamen, 2026)
The rapid development of digital technology has significantly influenced various aspects of human life, including the construction and dissemination of religious discourse. Digital media no longer function merely as channels of information, but also as spaces for meaning-making that shape how society understands religious values. One platform contributing to the construction of religious discourse in the digital sphere is LINE Webtoon. This study aims to analyze the representation of Islamic preaching (da’wah) messages in the slice-of-life Islamic-themed Webtoon KURMA using the semiotic approach of Roland Barthes, particularly his concept of two orders of signification (denotation and connotation). This research employs a qualitative descriptive method with semiotic analysis of selected scenes from the first episode of Webtoon KURMA. The findings reveal that the webtoon embeds Islamic values through the representation of everyday actions performed by its characters, such as caring for others, giving charity to those in need, sincerity in performing good deeds, and demonstrating social empathy. At the denotative level, these scenes depict ordinary acts of sharing and social interaction. However, at the connotative level, they convey religious meanings related to compassion, sincerity, and social solidarity rooted in Islamic teachings. At the level of myth, the webtoon constructs a cultural image of the ideal Muslim as generous, empathetic, and humanistic. Thus, Webtoon KURMA functions not only as entertainment media but also as a form of cultural da’wah in the digital era. Its light narrative style and visual storytelling enable Islamic values to be conveyed effectively without appearing doctrinal or didactic. This study highlights the strategic potential of digital comics as contextual and relevant media for communicating Islamic messages within contemporary digital society.